Exploring the Quantum: Atoms, Cavities, and Photons - Haroche, Serge; Raimond, Jean-Michel (Oxford Graduate Texts, 2006)
The counter-intuitive aspects of quantum physics have been illustrated for some time by thought experiments, from Einstein's photon box to Schrödinger's cat. These experiments have now become real, with single particles — electrons, atoms or photons — directly unveiling the weird features of the quantum. State superpositions, entanglement and complementarity define a novel quantum logic that can be harnessed for information processing, raising great hopes for applications. This book describes a class of such thought experiments made real. Juggling with atoms and photons confined in cavities, ions or cold atoms in traps, provides an incentive to shed a new light on the basic concepts of quantum physics. Measurement processes and decoherence at the quantum-classical boundary are highlighted.